2015
DOI: 10.5005/jp-journals-10024-1697
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effects of Dental Implants on Oral Lesions

Abstract: Implant treatment is best done with caution in patients with cancer or mucocutaneous disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 62 publications
3
13
0
Order By: Relevance
“…In particular, an increase of concentration of titanium ion, the main component of the implant, in the saliva may lead to types 1 and 4 inflammatory reactions and lead to burning mouth syndrome. In addition, studies on the association between dental implants and OML suggest that implants may be a risk factor for OLP and AR (7,24). The present study also showed that implants and prosthetics collectively accounted for 72-80% of the total treatment in OLP and AR patients in terms of the treatment rate; this finding is consistent with results of previous studies (Table 4) (7,24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In particular, an increase of concentration of titanium ion, the main component of the implant, in the saliva may lead to types 1 and 4 inflammatory reactions and lead to burning mouth syndrome. In addition, studies on the association between dental implants and OML suggest that implants may be a risk factor for OLP and AR (7,24). The present study also showed that implants and prosthetics collectively accounted for 72-80% of the total treatment in OLP and AR patients in terms of the treatment rate; this finding is consistent with results of previous studies (Table 4) (7,24).…”
Section: Discussionsupporting
confidence: 92%
“…The administration of compressed air during DT is also a possible contributing factor, as the oral mucosa is stimulated from the force of the dry air applied to certain regions susceptible to mucosal disease (5,6). The various stimuli that can be applied during these DTs have almost no effect on healthy adults (7). However, if persistent physical and chemical stimuli are applied to the oral mucosa in patients with early-stage oral mucosal disease (dry mouth), the elderly, or patients with impaired immune function or a debilitating disease, the oral epithelium may be affected, resulting in ulcers or an immunologic disease (8).…”
Section: Introductionmentioning
confidence: 99%
“…The study results were consistent with other reports and reviews, which stated that implant placement may exacerbate or cause recurrence of OLP away from or at the implant site in previously treated patients . However in this study, implant placement in the control group did not cause or exacerbate any extra lesions in relation to the noncontrolled group.…”
Section: Discussionmentioning
confidence: 94%
“…This approximated the inflammatory infiltrate directly over the marginal bone and focused the by‐products directly to the implant collar region, causing accelerated bone loss, at a rate of 2.5 mm MBL every 4 years. The clinical service time of implants in patients with active LP is expected to be reduced to almost 8 years …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation